Physiochemical characterization and anticancer efficacy of camptothecin loaded β-Cyclodextrin-EDTA-Fe₃O₄ nanocarrier - Krishnan, Poorani (2017)
Camptothecin (CPT) is a distinguished anticancer drug that effectively works on various cancers particularly colon cancer. Camptothecin is naturally occurring alkaloid that has significant amount of anti-tumor activity. However, poor solubility and instability of CPT has greatly restricted its chemotherapeutic value. Thus, various nanocarriers are continuously being formulated and designed to enhance the delivery, solubility, stability and bioavailability of CPT. As such, in the present study, we studied and determined the fabrication of novel magnetic nanocarrier by the combination of ß-Cyclodextrin-EDTA-Fe3O4 magnet ic nanoparticle(CEF) conjugated with CPT. This nanocompound CPT-CEF were synthesized with the objective to enhance CPT’s stability, bioavailability and subsequently improve its therapeutic value through the use of nanocarrier (CEF).Both β-Cyclodextrin and Fe3O4 magnetic nanoparticle are increasingly utilized in pharmaceutical application due to its promising therapeutic value. In this study, this hybrid nanocarrier was comprehensively characterized by NMR spectrometers and scanning electron microscopy. Particle size analysis, zeta potential measurements, drug loading efficiency and in-vitro drug release study was also performed to characterize CPT-CEF. The magnetic nanocarrier exhibited decent improvement in the stability of CPT encapsulated nanocarrier. Additionally in vitro drug release study exhibited the ability of CPT-CEF to solubilize in both acidic and neutral environment. The ability of CPT-CEF to reflect on the anticancer activity of encapsulated CPT through the induction of apoptosis in HT29 colon cancer cells was also evaluated. MTT assay was used to show dose dependent cytotoxicity of CPT-CEF. Cell cycle analysis, Annexin V-FITC/PI staining, mitochondrial membrane depolarization (JC-1), caspase-3 activity assay were performed to detect apoptosis and cell cycle arrest.CPT-CEF evidently showed a dose-dependent cell viability reduction in HT29 cell line. CPT-CEF also effectively induced apoptosis, which was determined by Annexin V/FITC staining. Mitochondrial membrane depolarization and activation of caspase-3 were also observed in response to CPT-CEF treatment. Interestingly cell cycle arrest was observed in the G1 phase indicating the possibility of synergistic effect contributed by the nanocarrier (CEF) on the action of CPT. These results suggests that CPT-CEF formulation has successfully maintained the anticancer potential of CPT while improving the stability and bioavailability CPT. These data suggests that CPT-CEF design has the potential to be developed as a major nanocarrier for camptothecin delivery for an effective treatment of colon cancer.